High-Performance Differential Imaging via Reconfigurable Black Phosphorus p–n Homojunction Optoelectronics - Hao, Rui; Luo, Lili; Yang, Lu; Yang, Xue; Gao, Fengsong; Zhu, Meijie; Li, Yingtao; Feng, Qingliang; Zhang, Zemin (Nano-Micro Letters, 2026)
The advancement of differential imaging and adaptive machine vision demands hardware capable of dynamic signal modulation, yet traditional photodetectors are limited by static doping profiles and fixed junction polarities. To overcome this bottleneck, we present a reconfigurable black phosphorus (BP) p–n homojunction photodetector engineered via in situ ferroelectric domain programming. By leveraging the non-volatile ferroelectric field of a bismuth ferrite substrate, we achieve precise, nondestructive modulation of the BP band structure, allowing for reversible switching between p–n and n–p configurations within a single device channel. This ferroelectric doping strategy effectively eliminates interface damage associated with ion implantation while enabling programmable rectification behaviors. The device demonstrates self-powered operation with a responsivity of 44 mA W−1 at 808 nm under zero-bias conditions. Crucially, we demonstrate a single-pixel imaging prototype where the reconfigurable junction polarity enables tunable edge sharpness and high-fidelity image reconstruction. This work establishes a paradigm for ferroelectrically programmable 2D devices, providing a versatile platform for differential imaging and contrast-enhancement optoelectronic applications. Highlights: 1 Ferroelectric BiFeO3 gating dynamically switches the black phosphorus (BP) homojunction between p–n and n–p states, enabling non-volatile reconfiguration. 2 BP/BiFeO3 heterostructure achieves broadband self-powered photodetection from 365 to 1550 nm, with responsivity ranging from 44 mA W–1 (808 nm) to 1.6 A W−1 (425 nm) and specific detectivity up to 1.8×1012 Jones. 3 Differential imaging leverages reversible p–n/n–p polarity switching to cancel common-mode static noise and enhance edge detection in near-infrared imaging.